2017
DOI: 10.1177/1934578x1701201140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Phenolic Compounds in Seven Hypericum Species and Their Antioxidant Properties

Abstract: A comparative analysis of the phenolic compounds in the 70% EtOH extracts of Hypericum acutum, H. androsaemum, H. barbatum, H. hirsutum, H. maculatum, and H. richeri has been carried out using high-performance liquid chromatography coupled with photodiode array UV detection and high resolution TOF mass spectrometry. Quercetin, astilbin, I3,II8-biapigenin, orientin, 2''-O-acetylorientin, three phenolcarboxylic acids, and eight flavonols 3-Oglycosides were identified in the extracts on the basis of their on-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…The HYP concentrations in the extracts analyzed in this study are generally high; they are several times higher (in the case of the leaves collected in the heathlands) than the values (2.92 mg g −1 ) reported by Olennikov and Chekhirova [25]. The HYP concentrations obtained from the leaves collected in the heathlands are similar to values shown in raw material of Hypericum perforatum, which is a hyperoside-rich species (15.5 mg g −1 ), by Zdunic et al [56]. Some bearberry samples were characterized by the content of hyperoside >7 mg g −1 .…”
Section: Characteristics Of Secondary Metabolitessupporting
confidence: 79%
“…The HYP concentrations in the extracts analyzed in this study are generally high; they are several times higher (in the case of the leaves collected in the heathlands) than the values (2.92 mg g −1 ) reported by Olennikov and Chekhirova [25]. The HYP concentrations obtained from the leaves collected in the heathlands are similar to values shown in raw material of Hypericum perforatum, which is a hyperoside-rich species (15.5 mg g −1 ), by Zdunic et al [56]. Some bearberry samples were characterized by the content of hyperoside >7 mg g −1 .…”
Section: Characteristics Of Secondary Metabolitessupporting
confidence: 79%
“…Despite numerous studies and publications, Hypericum species are of high-priority research due to the increasing pharmacological significance and commercial value of Hyperici herba, officially obtained from H. perforatum (Stojanovic et al, 2013). Thus, a number of Hypericum species from different countries of the world, such as Brazil (França et al, 2013), Greece (Mathioudaki et al, 2018), Italy (Mandrone et al, 2017), Tunisia (Hosni et al, 2017), Serbia, Montenegro (Zdunic et al, 2017), Portugal (Nogueira et al, 2008), Lithuania (Bagdonaite et al, 2010), Jordan (AI-Rifaee et al, 2010), Iran (Pirbalouti et al, 2014), Peru (Ccana-Ccapatinta et al, 2014, and Turkey (Cirak et al, 2016a(Cirak et al, , 2016b(Cirak et al, , 2017a(Cirak et al, , 2017b have been investigated in respect to the presence of chemical ingredients that give health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Standard compounds were used for the identification of chlorogenic acid (1), rutin (2), hyperoside (3), isoquercitrin (4), quercetin (5), and hypericin (6). The identification of the rest of the compounds (Table 1) was performed by comparison of their mass and UV-vis spectra to those in the literature (peaks 6, 7, 9, 13, 16, 19, 20, 21) (Brolis et al 1998;Tatsis et al 2007;Porzel et al 2014;Zdunic et al 2017;Sarrou et al 2018;Napoli et al 2018); peaks 2-5, 18, and 23-26 were identified at the compound class level and their presence in other Hypericum taxa has been reported earlier (Tanaka et al 2009;Mamemura et al 2011;Porzel et al 2014;Sarrou et al 2018). The spectra of peaks 15 and 17 were the same; HPLC analysis showed that peak 15 had the same elution time with I3,II8-biapigenin (7) in H. perforatum extract (Zeliou et al 2017).…”
Section: Resultsmentioning
confidence: 99%